Mengintegrasikan teknologi informasi dalam perencanaan pengembangan Desa Wisata Pujon Kidul yang berkelanjutan - Aisyah, Siti (Maliki Interdisciplinary Journal, 2024)
Pujon Kidul Tourism Village is a tourist destination located in Malang district which is famous for its beautiful natural panorama and culture of the local population. This village has become a favorite destination for domestic and foreign tourists because of its increasing popularity as a tourist destination. However, even though it is increasingly popular, the Pujon Kidul Tourism Village is currently facing challenges related to the use of information technology which is one of the factors inhibiting the transition to a sustainable information technology-based tourism village. This research aims to integrate information technology into the development planning of the Pujon Kidul tourist village to create a sustainable tourism village development model. The research method used in this research is qualitative using descriptive methods and SWOT analysis. Based on data obtained through research, four main strategies can be designed to be used in developing the Pujon Kidul Tourism Village. First, the strategy of using a geographic information system (SIG) to plan and manage tourist villages. Second, the strategy is to use digital platforms for marketing and ordering. Third, strategy for using digital platforms for marketing and ordering. The fourth strategy is to empower local communities through training and education to improve service quality and ensure active participation and fair economic benefits for all local communities in the Pujon Kidul Tourism Village. Specifically, this research provides benefits for the Pujon Kidul Tourism Village in terms of tourism village development strategies, showing that the integration of information technology plays an important role in achieving tourism village development based on technological sustainability and competitiveness.